PERTUMBUHAN TANAMAN BUAH NAGA (Hylocereus undatus L.) YANG DIBERIKAN BERBAGAI KONSENTRASI NAA (Napthalen Acetic Acid) SECARA IN VITRO - Ramal Yusuf; Syamsuddin Laude Laude; Hawalina Hawalina; Ni Made Setianingsih (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
The research aimed to gain the appropriate NAA concentration in performing tissue culture of dragon fruit plants. The research was compiled by using completely randomized design consisting of 4 treatments and each treatment was repeated 6 times that 24 experimental units were done. The variables observed include the number of shoots, the number of roots, the number of segments, and the length of shoots observed at the age of 4 weeks and 8 weeks after planting. The research findings reveal that on the observation at 4 weeks after planting the NAA concentration has effect on the number of segments and the elongation of shoots, yet it does not have effect on the number of shoots and roots, while at 8 weeks after planting the NAA concentration has effect on the number of shoots, the number of roots, the number of segments, and the length of shoots. The research findings also show that the treatment of N3 (0.3 ppm NAA) gives better result compared with other treatments in which the average number of shoots formed is 5.50 per explant, the number of roots formed is 3.50 per explant, the number of segments formed is 8.83 per explant and the average length of shoots formed is 2.13 cm per explant. Key Words : Dragon Fruit, NAA Concentration, In Vitro.